A Study of the Academic Achievement in Information Technology on the Topic of "Getting to Know Computers" Among Fourth-Grade Students Using an Electronic Textbook (E-Book) - Prasanpot, Wanwiwa; Limtasiri, Oranuch (Journal of Buddhist Education and Research (JBER), 2025)
This study aims to (1) develop and evaluate the effectiveness of an electronic book (E-book) based on the 80/80 efficiency criterion and (2) analyze the learning achievement of 4th-grade students after using the E-book as an instructional tool. The population and sample for this experiment consisted of 60 fourth-grade students from Hin Tok Municipality Demonstration School during the second semester of the 2024 academic year. The selected sample group included 20 students from Class 4/1, chosen through purposive sampling. The research employed a one-group experimental design with a pretest-posttest approach (One-group Pretest-Posttest Design). The research instruments included (1) the E-book titled "Introduction to Computers" from the Information Technology series, (2) a lesson plan on Information Technology, and (3) an achievement test on Information Technology focusing on Introduction to Computers. The findings revealed that (1) the E-book demonstrated an efficiency level of 80.25/85.11, meeting the 80/80 criterion, and (2) students’ learning achievement after using the E-book was significantly higher than before at the .05 statistical significance level.